THE INCOME TAX–COLLECTION ASPECTS. - Mires, H. F. (The Accounting Review, 1928)
Abstract With a view to giving the best possible service to the taxpaying public and for the purpose of protecting interests of the U.S. Government, more than 5,000 employees of the U.S. Internal Revenue Services attached to the Collection Service have been stationed at strategic points throughout the U.S. and its possessions. Most of these employees have been selected from the Civil Service registers. Others who are not required to qualify by Civil Service examinations must meet certain requirements in the way of previous education, training and experience in revenue matters. In connection with the collection of internal revenue taxes, two separate and distinct methods are employed. The first and older method is by the sale of internal revenue stamps. The other method of collecting the revenue is by means of tax assessment. The amount of internal revenue which is paid annually into the Treasury is affected to a great extent by the general prosperity of the country, and this is duly reflected in the prosperous condition of the U.S.